2016
DOI: 10.4269/ajtmh.16-0485
|View full text |Cite
|
Sign up to set email alerts
|

Animal Husbandry Practices and Perceptions of Zoonotic Infectious Disease Risks Among Livestock Keepers in a Rural Parish of Quito, Ecuador

Abstract: Abstract. Small-scale livestock production plays an essential role as a source of income and nutrition for households in low-and middle-income countries, yet these practices can also increase risk of zoonotic infectious diseases, especially among young children. To mitigate this risk, there is a need to better understand how livestock producers perceive and manage risks of disease transmission. Twenty semistructured, in-depth interviews were conducted with small-scale livestock producers in a semirural parish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 43 publications
4
66
0
Order By: Relevance
“…1,7,13,14 In Ecuador, one study found that nearly half of the producers considered the use of antibiotics important for growth promotion, especially when animals are young. 15 This intensive use of antibiotics has many implications, including greater AMR gene richness and lower taxonomic diversity compared with backyard chickens. 14 Small-scale introductions of intensively raised food animals over a short duration may yield lasting effects on the surrounding environment.…”
Section: Backyard Chickens Broiler Chickensmentioning
confidence: 99%
“…1,7,13,14 In Ecuador, one study found that nearly half of the producers considered the use of antibiotics important for growth promotion, especially when animals are young. 15 This intensive use of antibiotics has many implications, including greater AMR gene richness and lower taxonomic diversity compared with backyard chickens. 14 Small-scale introductions of intensively raised food animals over a short duration may yield lasting effects on the surrounding environment.…”
Section: Backyard Chickens Broiler Chickensmentioning
confidence: 99%
“…Emelda et al (2014) and Rouf et al (2014) report that Asian countries including Indonesia import young bulls because they have a comparative advantage in producing beef cattle, due to the availability of agro-industry by-products and relatively low labor wages. Guzek et al (2015) and Lowenstein et al (2016) state that the comparative advantages of the livestock sub-sector are contributed by the potential of livestock resources and natural resources in providing feed.…”
Section: Pam Analysis Of Bali Cattle Farm Businessmentioning
confidence: 99%
“…In LMICs, antimicrobials are often available over the counter in animal agriculture shops ( Katakweba et al 2012 ). The practice of using antimicrobials in small-scale food animal production—whether for growth promotion, disease prevention, or disease treatment—has been documented in a diverse set of studies within LMICs ( Andoh et al 2016 ; Braykov et al 2016 ; Katakweba et al 2012 ; Lowenstein et al 2016 ; Nguyen et al 2015 ; Nonga et al 2010 ; Roess et al 2013 ) ( Table 1 ). In rural Ecuador, for example, small-scale poultry farmers report that they regularly administer antimicrobials, including drugs from six different antimicrobial classes ( Braykov et al 2016 ).…”
Section: Antimicrobial Use In Small-scale Food Animalsmentioning
confidence: 99%
“… Conceptual illustration of AMR spillover from small-scale food animals to humans ( Lowenstein et al 2016 ; Roess et al 2013 ; Braykov et al 2016 ; Andoh et al 2016 ; Pehrsson et al 2016 ; Moser et al 2017 ). …”
Section: Introductionmentioning
confidence: 99%